Pemberian Edukasi Perilaku Hidup Bersih dan Sehat (PHBS) Bagi Kualitas Psikologis Anak Binaan di Lembaga Pembinaan Khusus Anak Kelas II Jakarta - Arzethy, Putri Laura; Muhammad, Ali; Anwar, Umar (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Clean and Healthy Living Behavior (PHBS) is one of the basics in recognizing and understanding how to maintain the health of each individual. The Juvenile Detention Center (LPKA) at Jakarta Class II as an institution for Children in conflict with the law (ABH) certainly does not escape providing education on the importance of PHBS during its detention period. However, based on the results of field observations through the implementation of a gradual questionnaire taking a population of 26 assisted children, it was found that assisted children experienced limitations in sanitation and hygiene facilities and infrastructure, which affected their clean living behavior while in Juvie. The method used by the Cadets in implementing this service practicum is the Community Development Method in assisting The Juvenile Detention Center at Jakarta Class II which aims to achieve increased implementation of Clean and Healthy Living Behavior by using collaboration and socialization or counseling techniques, namely the Cadets together with The Juvenile Detention Center at Jakarta Class II collaborates together to carry out activities using socialization or counseling techniques to increase the awareness and motivation of target children in implementing Clean and Healthy Living Behavior despite limitations. At the end of the practicum, there was an increase in awareness and personal hygiene activities by the target children in implementing Clean and Healthy Living Behavior while at The Juvenile Detention Center.